The misrepresented claims Of David Samuel Margoliouth On Prophet Muhammad’s Miracles: a critical evaluation - Akilu, Muhammad Aliyu; Abdul Rahim, Adibah (Universiti Sains Islam Malaysia, 2018)
This paper attempts to evaluate the misrepresented claims of the Western orientalist, David Samuel Margoliouth on the miracles of Prophet Muhammad (p.b.u.h). Like most Christian scholars, Margoliouth claimed that only Biblical prophets wrought a number of miracles to validate their truth, and Prophet Muhammad (p.b.u.h) possessed no miracle including the Qur’an. To justify his claim, Margoliouth asserted that even the Qur’an clearly points out that the Prophet (p.b.u.h) was never given any miracle, and hence, Muslims’ claims that he performed many physical miracles were just inaccurate and groundless. In attempt to evaluate the misrepresented claims of Margoliouth, this paper examines his main evidences and observations. At the same time, it deliberates a critical investigation of historical Islamic data about the miracles of Prophet Muhammad (p.b.u.h) in order to point out the validity of those miracles. Based on the historical facts, it can be justifiably claimed that Margoliouth’s rejection of Prophet’s miracles was part of his misrepresentation of Islam.